Thyroid Ultrasound Elastography: A Promising Undeniably Diagnostic Tool for Predicting the Risk of Malignancy - Rahman, Hafizur (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Thyroid disease is of common occurrence, especially in iodine deficient areas. Thyroid nodules are common findings in the general population. It is important to distinguish the subset of thyroid nodules that are malignant, as morbidity and mortality from thyroid cancer increases with disease stage. B-mode ultrasound features are initially used to select thyroid nodules for FNA. Although FNA is considered the gold standard for diagnosis, it is yet imperfect as up to 15- 30% of samples are considered non-diagnostic or indeterminate. Thyroid ultrasound elastography(USE) is a noninvasive method of assessing thyroid nodules that provides complementary information to B-mode ultrasound and FNA. The combined use of thyroid USE with B-mode ultrasound may improve the ability to discriminate benign from malignant thyroid nodules and reduce the number of needed FNAs. Thyroid USE may also aid with the difficult problem of distinguishing between malignant and benign follicular neoplasm.The elastic properties of tissue have always been of interest in clinical practice. In the past, the identification of structures that were stiffer on physical palpation would raise the suspicion. With the development and advancement of medicine, there proved to be a true correlation in the prediction of malignancy of lesion: malignant disease tends to stiffen the affected tissue, either by increased cell proliferation or fibrosis. Palpation is the oldest method for the detection of thyroid nodules, which if informed by the knowledge that malignant thyroid lesions tend to be much harder than benign ones. Palpation is dependent on the size, location and skill of the physician. Nodules are very small or located in deep regions; there detection by palpation is difficult or even impossible. Although malignant lesion differs in terms of elasticity, it may not have echogenic properties, preventing its detection by conventional ultrasound. Imaging that indicates the stiffness or deformation related to their structural formation. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):96-98